The universe - William Collins (london: william collins, 2021)
Every night, above our heads, a drama of epic proportions is playing out. Diamond planets, zombie stars, black holes heavier than a billion Suns. The cast of characters is extraordinary, and each one has its own incredible story to tell. We once thought of our Earth as unique, but we have now discovered thousands of alien planets, and that's barely a fraction of the worlds that are out there. And there are more stars in the Universe than grains of sand on every planet in the Solar System. But amid all this vastness, the Milky Way Galaxy, our Sun and the Earth are home to the only known life in the Universe - at least for now. With a foreword from Professor Brian Cox, and access to all the latest stunning NASA photography, Andrew Cohen takes readers on a voyage of discovery, via the probes and telescopes exploring the outer reaches of our galaxy, revealing how it was formed and how it will inevitably be destroyed by the enigmatic black hole at its heart
for Teachers
Keywords: Astronomy